How to Date a Flying Mexican : New and Collected Stories - Olivas, Daniel A. (Book collections on Project MUSE., 2022)
"The book is a collection of Daniel A. Olivas' distinct, Chicano short stories-sharing once again some of his best-loved, unforgettable and somewhat strange tales and also introduces readers to new stories. The characters and episodes in the book explore worlds of magic, fairy tales, fables and dystopian futures and confront questions of morality, justice, and self-determination while being deeply steeped in Chicano and Mexican culture"--